The Influence of Leadership Style, Work Environment and Competency on Employee Performance - Saripah, Melda; Ismartaya; Samsuri (International Journal of Managemen Analytics (IJMA), 2024)
This research aims to determine the influence of leadership style, work environment, and competence on the performance of PT employees. Rentokil Bogor City. The sample of 69 employees was taken using the Taro Yamane formula. The analytical method used in the research is descriptive and verification methods. Data collection techniques through questionnaires, observation, interviews and literature study. Data analysis uses multiple regression analysis, coefficient of determination analysis, F test and t test. The results of the research simultaneously show the influence of leadership style, work environment and competence on the performance of PT. Employees Rentokil Bogor City. Partially, leadership style, work environment and competence have a positive and significant effect on employee performance.